A topology survey of single-stage power factor corrector with a boost type input-current-shaper. - Qiao, C. (IEEE Transactions on power electronics)
A topological review of the single stage power factor corrected (PFC) rectifiers is presented in this paper. Most reported single-stage PFC rectifiers cascade a boost-type converter with a forward or a flyback DC-DC converter so that input current shaping, isolation, and fast output voltage regulation are performed in one single stage. The cost and performance of single-stage PFC converters depend greatly on how its input current shaper (ICS) and the DC-DC converter are integrated together. For the cascade connected single-stage PFC rectifiers, the energy storage capacitor is found in either series or parallel path of energy flow. The second group appears to represent the main stream. Therefore, the focus of this paper is on the second group. It is found that many of these topologies can be implemented by combining a two-terminal or three-terminal boost ICS cell with DC-DC converter along with an energy storage capacitor in between. A general rule is observed that translates a three-terminal ICS cell to a two-terminal ICS cell using an additional winding from the transformer and vice verse. According to the translation rule, many of the reported single-stage PFC topologies can be viewed as electrically equivalent to one another. Several new PFC converters were derived from some existing topologies using the translation rule